Perception of Harms and Benefits of Electronic Cigarettes Among Adult Malaysian Men: A Comparison by Electronic Cigarette Use and Smoking Status. (October 2019) - Chan, Caryn Mei Hsien; Ab Rahman, Jamalludin; Tee, Guat Hiong; Wee, Lei Hum; Ho, Bee Kiau; Robson, Noor Zurani Md Haris; Draman, Shamsul; Ling Miaw Yn, Jane; Kuang Hock, Lim; ,; Yusoff, Muhammad Fadhli; Kartiwi, Mira; et al.
Little is known about the perceptions of harm and benefit associated with the use of e-cigarettes in Malaysia. This was a cross-sectional analysis of a nationally representative sample comprising 1987 males (≥18 years of age). Current, former, and never users of conventional cigarettes and/or e-cigarettes participated in a questionnaire study conducted via face-to-face interviews. The relationship between participant characteristics and perceptions of harm and benefit of e-cigarettes were determined with multivariable logistic regression. There were 950 current, 377 former, and 660 never users of e-cigarettes. Government employees (odds ratio [OR] = 1.85, 95% confidence interval [CI] = 1.29-2.66, P = .001), private sector employees (OR = 1.67, 95% CI = 1.27-2.18, P = .001), and the self-employed people (OR = 1.68, 95% CI = 1.31-2.17, P = .001) were more likely to perceive e-cigarettes as more harmful than conventional cigarettes compared with respondents who were not wage earners. All current users in the form of e-cigarette users (OR = 7.87, 95% CI = 3.23-19.18), conventional cigarette smokers (OR = 1.80, 95% CI = 1.39-2.33), and dual users (OR = 8.59, 95% CI = 4.76-15.52) were more likely to perceive e-cigarettes as useful in quitting conventional cigarette smoking compared with former and never users. Our findings constitute an important snapshot into the perceptions of e-cigarette harms and benefits, which could inform targeted public health messaging strategies.